OPTN/SRTR 2019 Annual Data Report: Intestine. Issue 2 (17th February 2021) - Horslen, S. P.; Smith, J. M.; Ahn, Y.; Skeans, M. A.; Cafarella, M.; Noreen, S. M.; Snyder, J. J.; Israni, A. K.
Abstract: Intestine transplant can be life‐saving and can improve quality of life for patients with intestinal failure. Medical and surgical advances in treatment of intestinal failure over the past 10 to 15 years have resulted in fewer patients being added to the waiting list for intestine transplant alone or for intestine transplant in combination with liver transplant (and sometimes other organs). Consequently, fewer transplants are being performed. The numbers of listings and transplants fell to new lows in 2019. The number of programs performing transplants in at least one patient in 2019 was the lowest in the last decade, equal to 2014, at 15. Graft failure plateaued over the past decade, but early graft loss has increased in the past 2 years, notably in recipients of a combined liver and intestine allograft. Five‐year patient survival for transplants in 2012‐2014 varied little by graft type.